2022
DOI: 10.1007/s00044-022-02953-4
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and biological evaluation of pyrazolo-benzothiazole derivatives as a potential therapeutic agent for the treatment of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative age related brain disease which diminishes learning and memory.Two common cholinesterases (ChEs), rst acetylcholinesterase (AChE) and second one butyrylcholinesterase (BChE) are the main targets to treat this disease. In the current paper, six novel pyrazolo-benzothiazole analogs were systematically planned, synthesized, and biological tested for their ChEs activities, antioxidant, enzyme kinetic, self induced Aβ modulation, PAMPA-BBB, and docking and molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…AD is a chronic age‐related brain disease characterized by the gradual cognitive decline, memory loss, excessive neuronal loss, and memory functions (Kumar, Goyal et al, 2022; Shi et al, 2021; Ying He et al, 2023). It is coupled with excessive loss of the neurotransmitter ACh causing dementia symptoms and leading to permanent memory loss over the period of time.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…AD is a chronic age‐related brain disease characterized by the gradual cognitive decline, memory loss, excessive neuronal loss, and memory functions (Kumar, Goyal et al, 2022; Shi et al, 2021; Ying He et al, 2023). It is coupled with excessive loss of the neurotransmitter ACh causing dementia symptoms and leading to permanent memory loss over the period of time.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Molecular docking studies also indicate that this compound fits fully into the active sites of h AChE. [ 46 ] Compounds D shows inhibitory activity against both enzymes MAO‐A and MAO‐B, with IC 50 values of 17.00 ± 0.89 and 2.95 ± 0.09 μM, respectively. [ 47 ] Therefore, synthesis of derivatives based on benzo[ d ]thiazole heterocycles is an active area of research.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Kumar et al synthesized pyrazolo-benzothiazole analogs and analyzed their acetylcholine esterase and antioxidant activities. [17] Additionally, a recent investigation of the benzothiazole-based derivatives aimed to evaluate the anticancer properties against Michigan Cancer Foundation-7 (MCF-7) and hepatoblastoma cell line (HepG-2). [18] The cancer studies of BTA analogs have reported naphthalimide derivatives with unique benzothiazole and thiazole moieties, as well as benzofuran or benzothiazole bis-thiazole hybrid derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Kumar et al. synthesized pyrazolo‐benzothiazole analogs and analyzed their acetylcholine esterase and antioxidant activities [17] . Additionally, a recent investigation of the benzothiazole‐based derivatives aimed to evaluate the anticancer properties against Michigan Cancer Foundation‐7 (MCF‐7) and hepatoblastoma cell line (HepG‐2) [18] .…”
Section: Introductionmentioning
confidence: 99%